2002
DOI: 10.1046/j.1365-2044.2002.02509_1.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of physicians' attitudes to transfusion practice in critically ill patients in the UK

Abstract: SummaryThis study aimed to examine the attitudes of intensivists and haematologists to the use of blood and blood products using a scenario-based postal questionnaire. One hundred and sixty-two intensivists and 77 haematologists responded to the survey. In four scenarios, the baseline haemoglobin thresholds for red cell transfusion ranged from 6 to 12 g.dl )1. There was significant variation between scenarios (p < 0.005). Increasing age, high Acute Physiology and Chronic Health Status II score, surgery, acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…8,9 Therefore, blood should be transfused considering factors such as age, disease severity, and specific diagnoses. 6,7,10,11 Yet in a United Kingdom survey of transfusion practices with the critically ill, Boralessa et al 12 reported RBC transfusion triggers of 9 to 10 mg/dL. Another survey of European ICU transfusion practices found that the mean pretransfusion hemoglobin level of patients not actively bleeding was 8.5 mg/dL.…”
mentioning
confidence: 93%
“…8,9 Therefore, blood should be transfused considering factors such as age, disease severity, and specific diagnoses. 6,7,10,11 Yet in a United Kingdom survey of transfusion practices with the critically ill, Boralessa et al 12 reported RBC transfusion triggers of 9 to 10 mg/dL. Another survey of European ICU transfusion practices found that the mean pretransfusion hemoglobin level of patients not actively bleeding was 8.5 mg/dL.…”
mentioning
confidence: 93%
“…Surveys of transfusion practices have repeatedly documented the importance attributed to hemoglobin triggers. A survey conducted by Boralessa and colleagues (2) in 1998 using a modified version of the Canadian survey found that 72% of British respondents opted for a transfusion threshold between 90 and 100 g/L, and 96% stated that they would transfuse at least 2 RBC units. These authors documented that transfusion practice among British critical care physicians was similar to observations made 7 yrs earlier among Canadian physicians.…”
mentioning
confidence: 98%
“…Changing this ingrained practice pattern has proved difficult. More recent studies have shown little change in the attitude of physicians with less than 10% of intensivists and no hematologists considering single‐unit transfusions in various clinical scenarios …”
mentioning
confidence: 99%